Petrography and Mineralogy of the iron ore from Nawgwezany Mishao area– Shalair Valley, KRG - Iraq: Insights on the Genesis - Abdalla, Shahra Othman; Mirza, Tola A.; Salih, Namam (Iraqi Journal of Science, 2023)
Iron ore deposits have been identified from Nawgwezany Mishao in the Shalair Valley area within the Iraqi Zagros Suture Zone (IZSZ) at NE-Iraq. The iron ore is mainly hosted by the Shalair Metamorphic Rock Group calcschist. The transmitted and reflected light microscope study and X-ray diffraction of the calcschist revealed that the predominance minerals are calcite, and sillimanite, while muscovite, graphite, k-feldspar, and opaque mineral represent minor constituents. Meanwhile, skarn host rock as a second host rock shows the mineral assemblages of clinopyroxene, quartz, hornblende, epidote, plagioclase, sericite, garnet, and opaque minerals. The field and petrographical data indicated that the iron ore includes magnetite, hematite, pyrite, martite, goethite, and limonite. Magnetite and hematite constitute the predominant minerals of the ores, which display variable shape sizes (from < 1 cm to > 10 m) and chiefly occurred as massive, veins, veinlets, and disseminated grains. Based on some magnetite grains, filled veins in the host rocks support the hydrothermal ore-forming processes. The paragenetic sequence of iron ore and the presence of dendritic manganese texture on the surface of some of the skarn host rocks, as well as the petrographical identification of calcite twins in calcschist of types one and two, are the three reasons that point to the hydrothermal skarn origin of the iron ore. Overall field evidence, morphology, mineralogy, textures, calcite twins, and dendritic manganese texture on the surface of calcshist host rocks suggest that the Nawgwezany Mishao iron ore is related to the hydrothermal skarn deposit.